2015
DOI: 10.25077/jka.v4i2.313
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Arteriovenous Hemangioma Clinically Mimicking Pigmented Nevus

Abstract: Abstrak   Arteriovenous hemangioma (AH) adalah lesi jinak pembuluh darah kulit yang jarang, biasanya muncul pada kulit wajah berupa lesi tunggal, meninggi, papul merah, atau keunguan; kadang-kadang papul coklat. Dilaporkan satu kasus AH dengan gambaran klinis menyerupai nevus pada pasien perempuan yang berusia 19 tahun. Ini adalahkasus pertama di Bagian Ilmu Kesehatan Kulit dan Kelamin RS. Dr. M. Djamil Padang. Pasien datang dengan keluhan bintik hitam di lengan kanan bawah sejak satu bulan lalu. Pada pemeriks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…It was the first case of arteriovenous hemangioma with this clinical picture. 2 Akiyama et al reported four cases of arteriovenous hemangioma in patients with chronic liver disease and suggested the possible association of chronic liver dysfunction with the occurrence of arteriovenous hemangioma. 7 The case presented in this article is a 53-year-old man who presented with a skin colored, 1 × 1.3 cm nodular lesion on his nose for 15 years.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was the first case of arteriovenous hemangioma with this clinical picture. 2 Akiyama et al reported four cases of arteriovenous hemangioma in patients with chronic liver disease and suggested the possible association of chronic liver dysfunction with the occurrence of arteriovenous hemangioma. 7 The case presented in this article is a 53-year-old man who presented with a skin colored, 1 × 1.3 cm nodular lesion on his nose for 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Arteriovenous hemangioma is a benign vascular lesion which can be either congenital or acquired. Although the etiology is unknown, trauma, inflammation, and chronic irritation may be its predisposing factors 2,4 . Clinically it is a red or violaceous papule which is frequently asymptomatic but pruritus, pain and enlargement may be seen in some patients 2 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations